Successful induction of therapeutic urinary concentration by intravenous ganciclovir and oral valganciclovir with remission of adenoviral hemorrhagic cystitis after cord blood transplantation. (8th June 2018) - Yanagisawa, Toshimitsu; Saito, Shoji; Katsuyama, Yoshihiko; Hirabayashi, Koichi; Shigemura, Tomonari; Tanaka, Miyuki; Sakashita, Kazuo; Nakazawa, Yozo
Abstract: AdV11‐HC is one of the major complications after allogeneic HSCT in Japan. We previously reported that the intravenous infusion of ganciclovir was effective against AdV11‐HC in a post‐transplant patient. We here report a case of a 10‐year‐old boy who underwent cord blood transplantation for the treatment of relapsed lymphoblastic lymphoma. He developed AdV11‐HC with an elevated AdV load in his urine and blood on day 14 after HSCT. He was immediately treated with intravenous ganciclovir; he rapidly achieved a remission of AdV11‐HC with a decreased AdV load in his urine and blood. He remained in remission of AdV11‐HC, even after we switched ganciclovir to oral valganciclovir on day 63. A pharmacokinetics study of his urine revealed that therapeutic concentrations of ganciclovir could be achieved by both intravenous ganciclovir and oral valganciclovir. These findings suggested that both intravenous ganciclovir and oral valganciclovir could be promising alternatives for the treatment of AdV11‐HC in post‐transplant patients.